ANALYZE THE EFFECT OF HEALTH PROMOTION TRAINING OF DHF ON IMPROVING COUNSELING SKILLS OF HEALTH SERVICE PROVIDERS - Sulastyawati, Sulastyawati; Nataliswati, Tri; Hidayah, Nurul (Jurnal Keperawatan, 2011)
Health service providers as one source of information for the community has an important role in the accuracy of information received by the community as capital formation, especially in the field of health behavior. For that, not only the provision of knowledge of health service providers is needed in the success of an extension, but also the skill of health service providers is to convey information. The purpose of this study to analyze the effect of health promotion training of DHF on improvingcounseling skills of health service providers in the Sumberrejo Sidoluhur Lawang by using the randomized pretest-posttest one group design. Data were collected using observation sheets andanalyzed using the wilcoxon signed ranks test with ? < 0,05. The results showed 73,3% of DHF counseling skills sufficient prior training of health promotion, 20% less and 6,7% better. While the results obtained after training 53,3% had adequate counseling skills and 46,7% had good counseling skills. Using wilcoxon signed ranks test get ? = 0,021 which means there is the influence of health promotion training of DHF on improving counseling skills of health service providers in the Sumberrejo Sidoluhur Lawang.